MENCARI NILAI HORMAT DAN RUKUN PADA TAYANGAN OPERA VAN JAVA DI TRANS 7 - Setyowati, Retno Manuhoro; Setiawan, Yuliyanto Budi; Nora, Hastika Yanti (Universitas Semarang, 2012)
As a form of puppet people development standard, Opera Van Java (OVJ) which aired on Trans 7 can be regarded as puppets of the grip of revolution on a large scale given the characteristics of the OVJ them is to use the Indonesian language and do not use master narratives. OVJ phenomenon is developing a play slapstick tradition of Mataram who first appears. If all this a play performed on the dimensions of verbal (words / sentences), in this OVJ also other aspects of the thematic core of which is actors, morality story, characterization of his characters, costumes, music, and even setting the stage. Opera Van Java turned into popular culture in the form of puppet people are loaded with innovation and reintepretation.